2018
DOI: 10.1007/s12250-018-0050-1
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography, Transmission, and Viral Proteins of Nipah Virus

Abstract: Nipah virus (NiV), a zoonotic paramyxovirus belonging to the genus Henipavirus, is classified as a Biosafety Level-4 pathogen based on its high pathogenicity in humans and the lack of available vaccines or therapeutics. Since its initial emergence in 1998 in Malaysia, this virus has become a great threat to domestic animals and humans. Sporadic outbreaks and person-to-person transmission over the past two decades have resulted in hundreds of human fatalities. Epidemiological surveys have shown that NiV is dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 73 publications
0
41
0
1
Order By: Relevance
“…Habitat selection and behavioral differences can further limit contact, even if species are nominally sympatric 19 . Some viruses may spread environmentally between spatially-proximate species with no direct behavioral contact 20 , but generally, sharing is more likely among species with more ecological overlap 21 . Even among species in close contact, most spillovers are still a dead end; progressively smaller subsets of viruses can infect novel host cells, proliferate, and transmit onward in a new host 18 .…”
Section: Main Textmentioning
confidence: 99%
“…Habitat selection and behavioral differences can further limit contact, even if species are nominally sympatric 19 . Some viruses may spread environmentally between spatially-proximate species with no direct behavioral contact 20 , but generally, sharing is more likely among species with more ecological overlap 21 . Even among species in close contact, most spillovers are still a dead end; progressively smaller subsets of viruses can infect novel host cells, proliferate, and transmit onward in a new host 18 .…”
Section: Main Textmentioning
confidence: 99%
“…The fact that most of the areas affected by strain-specific mutations lie near the C-terminus of N protein (Figs. [3][4][5], which represent or are located in close proximity to the regions that bind to the P protein ( Fig. 5), suggests that the greater disorder of the more virulent strains may be involved in modulating the aforementioned functions of the viral proteins N, P, and L. It is likely that the regions of greater disorder found in the more virulent strains, such as that shown in pink in Fig.…”
Section: C-terminus Of N Protein Touches P Protein: the Focal Pointmentioning
confidence: 99%
“…Many of the pigs were initially infected by eating fruits that were partially eaten by fruits bats, which had left their virus-laden saliva behind (4)(5)(6). Upon isolation and sequencing of the virus, it was revealed that the culprit was a novel RNA virus from Paramyxoviridae family, which includes the Hendra (HeV), mumps (MuV), and measles (MeV) viruses [4][5][6][7]. The symptoms for Nipah infections often include an initial flu-like fever that often follows by irritations, coma, and then death.…”
Section: Introductionmentioning
confidence: 99%
“…SADS-CoV is probably the first bat-derived coronavirus that is found to infect pig directly in recent years. Pigs are regarded as mixing vessels and intermediate hosts of several viruses, such as avian influenza A viruses and Nipah virus (Sun et al 2018;Wang et al 2018). Given that a novel swine enteric coronavirus (SeCoV) is generated by the recombination of porcine transmissible gastroenteritis virus and PEDV, recombination between SADS-CoV and other swine coronaviruses cannot be excluded (Akimkin et al 2016;Boniotti et al 2016).…”
mentioning
confidence: 99%